2019
DOI: 10.1182/blood-2018-12-890236
|View full text |Cite
|
Sign up to set email alerts
|

HAP1 loss confers l-asparaginase resistance in ALL by downregulating the calpain-1-Bid-caspase-3/12 pathway

Abstract: l-Asparaginase (l-ASNase) is a strategic component of treatment protocols for acute lymphoblastic leukemia (ALL). It causes asparagine deficit, resulting in protein synthesis inhibition and subsequent leukemic cell death and ALL remission. However, patients often relapse because of the development of resistance, but the underlying mechanism of ALL cell resistance to l-asparaginase remains unknown. Through unbiased genome-wide RNA interference screening, we identified huntingtin associated protein 1 (HAP1) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Instead, it is possible that L‐ASP might induce metabolic alterations or instill other molecular changes that induce resistance to this protocol. Resistance to L‐ASP in human ALL can be induced by loss of huntingtin‐associated protein 1 . Huntingtin‐associated protein 1 interacts with other proteins to form a complex that mediates Ca 2+ release from the endoplasmic reticulum and through other mechanisms can decrease entry of external Ca 2+ into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is possible that L‐ASP might induce metabolic alterations or instill other molecular changes that induce resistance to this protocol. Resistance to L‐ASP in human ALL can be induced by loss of huntingtin‐associated protein 1 . Huntingtin‐associated protein 1 interacts with other proteins to form a complex that mediates Ca 2+ release from the endoplasmic reticulum and through other mechanisms can decrease entry of external Ca 2+ into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, activation of autophagy by L-asparaginase treatment has been found to protect ALL cells from death, even though it is still unclear whether intracellular asparagine levels can be restored through this mechanism or not [ 64 ] ( Figure 2 ). Another study using genome-wide RNAi screen identified huntingtin associated protein 1 (HAP1) as a biomarker and a driver for the sensitivity to L-asparaginase treatment [ 65 ]. As a result, loss of HAP1 confers resistance to L-asparaginase treatment through preventing the release of calcium from endoplasmic reticulum (ER) and the subsequent calcium-dependent cell death [ 65 ] ( Figure 2 ).…”
Section: Asparagine and L-asparaginase In Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%
“…Another study using genome-wide RNAi screen identified huntingtin associated protein 1 (HAP1) as a biomarker and a driver for the sensitivity to L-asparaginase treatment [ 65 ]. As a result, loss of HAP1 confers resistance to L-asparaginase treatment through preventing the release of calcium from endoplasmic reticulum (ER) and the subsequent calcium-dependent cell death [ 65 ] ( Figure 2 ). Indeed, pharmacogenetic and functional genomic approaches have been used to identified genes associated with L-asparaginase resistance/sensitivity in ALL patient samples or cell lines [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Asparagine and L-asparaginase In Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%
“…In addition, this study showed that the deprivation of Asn specifically determined a significant induction of zinc finger and BTB domain containing 1 (ZBTB1), which is a transcription factor involved in T cell development [117,118], whose loss was sufficient to sensitize resistant T-ALL cells to ASNase both in vitro and in vivo. ASNase resistance was also recently associated with huntingtin associated protein 1 (HAP1) expression in ALL cells through an experimental approached based on an unbiased genome-wide RNA interference screen [119]. Mechanistically, HAP1 interacts with huntingtin and the intracellular Ca 2+ channel, inositol 1,4,5-triphosphate receptor (IP3R), to form a ternary complex that mediates endoplasmic reticulum (ER) Ca 2+ release upon stimulation with inositol 1,4,5-triphosphate (IP3).…”
Section: Impaired Synthesis Of Asparagine As a Metabolic Vulnerabilitymentioning
confidence: 99%